Impact of Teaching Cognitive and Metacognitive Learning Strategies on Academic Achievement among Nursing Students - Naser Heidari; Sara Haghighat; Meysam Haji Mohammadi Arani; Fateme Ghorbani; Jamal Ashoori (Golestan University of Medical Sciences, 2016)
Background: Cognitive and metacognitive learning strategies are identified as important solutions for improving academic achievement. This study aimed toevaluate the effect of teaching cognitive and metacognitive learning strategies on academic achievement among nursing students. Methods: This Study was an experimental with pretest and posttest and follow-updesign.  The study population included all nursing students atIslamic Azad University of Pishva during 2013-14. Overall, 40 students were chosen byconvenience sampling technique and randomly divided into two groups (20 subjects in each group) of experimental and control. Students in the experimental group received 10 sessions of 70 minutes long (twice a week) training for cognitive and metacognitive strategies, while the control group received no training. All students completed a teacher-made academic achievement testat the pretest, posttest, and follow-up phases. Data were analyzed usingrepeated measures ANOVA technique. Results: The mean value of the experimental group (16.67 ± 3.58) was higher than the control group (13.47 ± 2.37) at the posttest phase. Themean value of the experimental group (16.29 ± 3.74) was higher than the control group (12.93 ± 2.84) at the follow-up phase. In addition, there were significant differencesbetween mean valuesat the posttest and follow up phases and mean valueatthe pretest phase. However, there was no significant difference between the mean values of the posttest phase and the follow-up phase. Conclusion: The results of this study indicate that teaching cognitive and metacognitive learning strategies improves academic achievement in students at posttest and follow-up phases. Thus, academic teachers may teach these useful strategies to the students to improve their academic achievement.